Genome-wide transcriptome analysis and drug target discovery reveal key genes and pathways in thyroid cancer metastasis - Zou, Minjing; Qattan, Amal; Al-Alwan, Monther; Ghebeh, Hazem; Binjumah, Naif; Al-Haj, Latifa; Khabar, Khalid S. A.; Altaweel, Abdulmohsen; Almohanna, Falah; Assiri, Abdullah M.; Aboussekhra, Abdelilah; Alzahrani, Ali S.; et al. (Frontiers in Endocrinology, 2025)
IntroductionMetastasis is the major cause of thyroid cancer morbidity and mortality. However, the mechanisms are still poorly understood. MethodsWe performed genome-wide transcriptome analysis comparing gene expression profile of metastatic thyroid cancer cells (Met) with primary tumor cells established from transgenic mouse models of papillary thyroid cancer (PTC), follicular thyroid cancer (FTC), poorly differentiated thyroid cancer (PDTC), and anaplastic thyroid cancer (ATC).ResultsGenes involved in tumor microenvironment (TME), inflammation, and immune escape were significantly overexpressed in Met cells. Notably, IL-6-mediated inflammatory and PD-L1 pathways were highly active in Met cells with increased secretion of pro-inflammatory and pro-metastatic cytokines such as CCL2, CCL11, IL5, IL6, and CXCL5. Furthermore, Met cells showed robust overexpression of Tbxas1, a thromboxane A synthase 1 gene that catalyzes the conversion of prostaglandin H2 to thromboxane A2 (TXA2), a potent inducer of platelet aggregation. Application of aspirin, a TXA2 inhibitor, significantly reduced lung metastases. Mertk, a member of the TAM (Tyro, Axl, Mertk) family of RTKs, was also overexpressed in Met cells, which led to increased MAPK activation, epithelial–mesenchymal transition (EMT), and enrichment of cancer stem cells. Braf-mutant Met cells developed resistance to BRAFV600E inhibitor PLX4720, but remained sensitive to β-catenin inhibitor PKF118-310.ConclusionWe have identified several overexpressed genes/pathways in thyroid cancer metastasis, making them attractive therapeutic targets. Given the complexity of metastasis involving multiple pathways (PD-L1, Mertk, IL6, COX-1/Tbxas1-TXA2), simultaneously targeting more than one of these pathways may be warranted to achieve better therapeutic effect for metastatic thyroid cancer.